Kennedy's blues : African-American blues and gospel songs on JFK - Rijn, Guido van, 1950- (American made music series., 2007)
Kennedy's Blues: African American Blues and Gospel Songs on JFK collects in a single volume the blues and gospel songs written by African Americans about the presidency of John F. Kennedy and offers a close analysis of Kennedy's hold upon the African American imagination. These blues and gospel songs have never been transcribed and analyzed in a systematic way, so this volume provides a hitherto untapped source on the perception of one of the most intriguing American presidents. After eight years of Republican rule the young Democratic president received a warm welcome from African Americans.